Lama Perendaman Terhadap Kadar Hidrogen Peroksida (H2O2) Pada Ikan Asin di Purwokerto Tahun 2019 - Tri Marthy Mulyasari; Susiyanti Susiyanti (Jurnal Sehat Mandiri, 2020)
Hydrogen Peroxide is not included in the list of food additives that are allowed in Minister of Health Regulation Number 033 of 2012 concerning Food Additives. Hydrogen peroxide is often used in fishery products such as salted fish to preserve and as a bleach. Hydrogen peroxide can dissolve in water. This study aims to analyze the effect of long immersion on hydrogen peroxide levels in salted fish. This research is a pre-experimental research.The sample in this study amounted to 9 samples with 3 times replication. Independent variable in this research is long immersion (1 hour, 2 hours, and 3 hours). Dependent variable in this research is hydrogen peroxide concentration in salted fish. Data analysis uses paired t test. The results of the analysis showed that the long immersion of 1 hour affected the reduction in H2O2 levels in salted fish with p values ​​of 0.015 (sample stockfish), 0.007 (sample jombrong), 0,000 (sample pethek). Long immersion of 2 hours affects the reduction in H2O2 levels in salted fish with a p value of 0.003 (sample stockfish); 0.007 (sample jombrong); 0.002 (sample pethek). Long immersion of 3 hours affects the reduction in H2O2 levels in salted fish with a p value of 0.001 (sample stockfish); p 0.003 (sample jombrong); p 0,000 (sample pethek). Immersion uses water significantly to reduce levels of hydrogen peroxide,then the community should wash salted fish with clean and flowing water before processing.